Hysterosalpingography Vs Hysteroscopy in the Detection of Intrauterine Pathology in Infertility - Shakya, B (Journal of Nepal Health Research Council, 2009)
Background: This study was to compare the accuracy of hysterosalpingography (HSG) with hysteroscopy (HSC) in detection of uterine pathology in patients with infertility. Methods: This is a prospective comparative study done among 50 new cases of primary and secondary infertility presenting to infertility clinic of Tribhuvan University Teaching Hospital from March 2006 - 2007. HSG was performed in the proliferative phase of menstrual cycle followed by HSC in the proliferative phase of the same or the following cycle. Intra uterine findings on HSG were evaluated and compared with hysteroscopic findings. Results: Out of 50 cases, HSG revealed normal findings in 49 cases (98%) and HSC demonstrated normal uterine cavity in 44 of the cases (88%). There was one abnormality (2%) shown on HSG (subseptate uterus) which was confirmed at HSC. HSC demonstrated six cases (12%) of intrauterine pathologies and these were endometrial polyps, subseptate uterus and submucous myoma. HSG in the detection of intrauterine pathology had a sensitivity (SV) of 16.7% (95% CI 0.9-63.5), specificity (SP) 100% (95% CI 90-100), positive predictive value (PPV) 100% (95% CI 5.5-100), negative predictive value (NPV) 89.8% (95% CI 77-96.2), false negative rate (FNR) 83.3% and accuracy rate (AR) 90%. Conclusion: HSG is a specific, but not sensitive predictor of uterine pathology. However, HSG did not provide any additional finding in comparison to HSC. Therefore, HSG is not advisable in the detection of uterine pathology in infertility patients.Key words: diagnostic hysteroscopy, hysterosalpingography, infertility, uterine cavity.   DOI: 10.3126/jnhrc.v7i1.2271 Journal of Nepal Health Research Council Vol. 7, No. 1, 2009 April 6-9